2010
DOI: 10.1145/1806895.1806900
|View full text |Cite
|
Sign up to set email alerts
|

Toward trusted wireless sensor networks

Abstract: This article presents the design and implementation of a trusted sensor node that provides Internet-grade security at low system cost. We describe trustedFleck, which uses a commodity Trusted Platform Module (TPM) chip to extend the capabilities of a standard wireless sensor node to provide security services such as message integrity, confidentiality, authenticity , and system integrity based on RSA public-key and XTEA-based symmetric-key cryptography. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…In [2], the concept is a TPM is presented with its architecture and all required components. [3] and [4] proposed a secure techniques on data aggregation, they focus on achieving the aggregation in a secure manner In [5] and [6], authors have proposed security solutions based on TPM. In [7], an authentication mechanism is proposed over WSN where nodes are equipped with TPM.…”
Section: Related Workmentioning
confidence: 99%
“…In [2], the concept is a TPM is presented with its architecture and all required components. [3] and [4] proposed a secure techniques on data aggregation, they focus on achieving the aggregation in a secure manner In [5] and [6], authors have proposed security solutions based on TPM. In [7], an authentication mechanism is proposed over WSN where nodes are equipped with TPM.…”
Section: Related Workmentioning
confidence: 99%
“…Some security protocols, such as Sizzle [7], advocate the use of the more resource efficient Elliptic Curve Cryptography (ECC) public key cryptosystem. Other research efforts, such as the SecFleck by Hu et al [8], provide support for faster RSA operations through hardware.…”
Section: Related Workmentioning
confidence: 99%
“…A CA may either be run by the administrator of the network or one of the established internet certificate authorities could be used. Hu et al showed that RSA, the most commonly used public key algorithm in the Internet, can be used in sensor networks with the assistance of a Trusted Platform Module (TPM) [8]. A TPM is an embedded chip that provides tamper proof generation and storage of RSA keys as well as hardware support for the RSA algorithm.…”
Section: A Standard Based End-to-end Security Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, scientists have tried to offer various network security solutions tailored to the limited resources WSN. These proposals includes: secure and efficient routing protocols [4], [1], secure data aggregation protocols [5], [6], [7], [8] and additional security mechanisms supported by Trusted Platform Module (TPM) [9], [10], [11], [12], [13], [14], [15].…”
Section: Introductionmentioning
confidence: 99%